Als Clinicus over de Grenzen van de Psychiatrie. De verwantschap tussen literatuur en wetenschap in het werk van de psychiater H.C. Rümke (1893-1967) - Kloosterman, Ingrid (Studium, 2010)
As a clincian beyond the boundaries of psychiatry. The congeniality of literature and psychiatry in the work of psychiatrist H.C. Rümke (1893-1967) One of the most important Dutch psychiatrists in the interwar period was H.C. Rümke (1893-1967). With his eclectic interest in psychiatric approaches such as both psychoanalysis and phenomenology, Rümke is most well known for his remarkable diagnostic and therapeutic skills. The life and work of Rümke has been studied in detail, most notably by the Dutch historian Jacob Van Belzen. Despite this extensive research, in this paper it is stated that a relevant aspect of Rümke’s work has been largely disregarded – namely his profound interest in and use of poetry and literature. Not only did Rümke write poems himself under the pseudonym of H. Cornelius, in his scholarly work he frequently refers to fictional literature and at the end of his career he wrote a comprehensive analysis of Frederik van Eeden’s novel Van de Koele Meeren des Doods. For the eclectic clinician Rümke literature and poetry are a source of knowledge to gain insight into the human psyche. Furthermore, according to Rümke, often literature succeeds better at expressing the human condition than the science of psychiatry can. In this article it is argued that for a coherent interpretation of the life and work of Rümke this literal and poetic aspect of his work cannot be disregarded. It is precisely Rümke’s profound interest in literature and poetry that reflects his two main theses about the science of psychiatry. These are on the one hand the centrality of clinical practice and on the other hand the boundaries of psychiatry. As a clinical practitioner Rümke’s aim was to be able to understand the suffering of the patient – literature and poetry could help him do that. Rümke’s use of literature and poetry can be understood by taking into account the context of the clinic, but the intertwinement between psychiatry, literature and poetry in Rümke’s work also reflects a broader issue. Namely that the science of psychiatry is not omnipotent and that sometimes the arts are better equipped to grasp the human condition.